Understanding student engagement with research: a study of pre-service teachers' research perceptions, research experience, and motivation. Issue 2 (14th March 2016) - Guilbert, Daniel; Lane, Rod; Van Bergen, Penny
Abstract : This study reports on findings from a research project that investigated the extent to which pre-service teachers at a major metropolitan Australian university engage with research, and the factors that influence their level of engagement or disengagement. Results from survey responses ( n = 235) and focus group interviews suggest that attitudes towards research are more positive among pre-service teachers who possess research experience and those who are intrinsically motivated with respect to their university studies. The article discusses the implications of these results for the effective organisation and promotion of research activities for pre-service teachers.